Penampilan Fenotipik Delapan Genotipa Jagung Lokal Manokwari Hasil Penggaluran Generasi Pertama - Nouke L. Mawikere; Amelia S. Sarungallo; Diyah A. Aribowo; Efa Gultom (Agrotek, 2015)
The objective of this study was to obtain the package information about the characteristics of first generation of eight genotypes of Manokwari-local corn which made strain based on seed color differences. The materials used in this study were eight genotypes of Manokwari-local corn, organic and inorganic fertilizers according to recommended dosage, and pesticides. Planting was done in the farmer’field located in Beach Amban, Manokwari. The study was designed using a single row and eight local corn genotipes which were planted in one seedbed with a size of 4m x 1.5m. Hybridization method used was artificially self-pollinating. The variables measured were plant- height character, stem character, leave character, cobs character, and seed character. Data analysis was done using T-test of the difference between the average value for each variable observed. Eight genotypes of Manokwari-local corn which have been evaluated on the characteristics of their vegetative and generative were vary. The highest percentage of seed color in a uniform cob was found in a population of Red-Kebar genotypes (94.4%) and the lowest in Purple-Anggi population (13.3%).